Automotive wheels - An approach for structural analysis and fatigue life prediction - De Carvalho, Cleginaldo Pereira; Voorwald, Herman Jacobus Cornelis [UNESP]; Lopes, Carlos Eduardo (SAE International, 2001)
Wheels are components working under cyclic loading and different load spectrum considering the load amplitude and frequency. Wheels can be considered an item of a vehicle security but restrictions about the weight are becoming strong for the OEM's. Depend on the manufacture process used of the wheels production the results in terms of Fatigue Life and weight relationship can be dramatically different. Based on different manufactured process an evaluation of fatigue life prediction can take account-using tests. The flowforming manufacturing process shows the best results comparing with the raw material hot rolled steel. Different types of wheels load prediction could be considered but a finite element method loading prediction shows the wheels loading spectrum and the influence of the flowforming manufacture process is taken account. Copyright © 2001 Society of Automotive Engineers, Inc.